Neoliberalism in the tourism and hospitality sector - Nadda, Vipin, 1970-; Sahidi, Bilan, 1964-; Azam, Muhammad, 1974-; Mulindwa, Dirisa (Business Science Reference, 2019)
"This book explores globalization from a tourism and hospitality context. It also evaluates whether globalization is a new form of colonization or a new form of economic cooperation between third world and developed countries"--